The American Frontier in Red Dead Redemption 2: An Interdisciplinary Perspective on Media and Literary Representation - Muh Sahrul Ardika Nai; Mas’ud Muhammadiah; Rosmawati Rosmawati (Fakultas Sastra, Universitas Bosowa, 2025)
This research examined the portrayal of the American Frontier in the video game Red Dead Redemption 2 using an interdisciplinary approach that integrated literary studies, textual analysis, semiotics, and hyperreality. The goal was to explore how the game constructed, adapted, and reimagined classic frontier themes such as survival, violence, freedom, and cultural conflict within a contemporary digital narrative. Employing Jean Baudrillard’s hyperreality theory and Charles Sanders Peirce’s semiotic model, the researcher analyzed specific dialogues and visual elements from the game’s script. The results indicated that Red Dead Redemption 2 blurred the lines between historical reality and simulation, creating a hyperreal depiction of the American West that echoed both cultural myths and modern interpretations. By framing the game as a contemporary literary work, this study highlighted the significance of video games as valuable sources of cultural expression and narrative depth. It also contributed to the broader application of literary analysis to digital media, suggesting that interactive storytelling plays a crucial role in shaping historical memory and identity